An Analytic Hierarchy Process Approach For Supplier Evaluation and Selection in a Steel Manufacturing Company - Tahriri, Farzad (2007)
Supplier selection is a complex problem involving qualitative and quantitative multicriteria. A trade-off between these tangible and intangible factors is essential in selecting the best supplier. This problem initiated when there are limitations in the capacity in which the managers are compelled to decide about two issues: which suppliers are the best and how much should be purchased from each selected supplier. Varieties of approaches have been applied, in the form of mixed integers, goal, and multi-objective programming to solve this problem. This approaches, being mathematical that have vital problems in considering qualitative factors. These study apply questionnaires to identifj and adopt the important criteria for supplier selection based on related studies by Dickson (1966), Weber (1991) and Zhang's (2003). In this work both tangible and intangible factors in choosing the best suppliers through analytical hierarchy process (AHP) were incorporated into Saaty's (1 980) proposed method. AHP process makes it possible to place the optimum order quantities among the selected suppliers, so that the total value of purchasing (TVP) becomes maximum. The Saaty's (1980) analytical hierarchy process (AHP) which is used in this case study can be useful in involving several decision makers with different conflicting objectives to arrive at a consensus decision. The main contribution of the study was identification of the important criteria for supplier selection process. The criteria found were Trust between key men, followed by net price and re-win percentage. Second contribution or findings was development of a multi-criteria decision model for evaluation and selection which is used for supplier selection in ABC steel company. Finally, the developed model is tested on four supplier selection problems. The results show the models are able to assist decisionmakers to examine the strengths and weaknesses of supplier selection by comparing them with appropriate criteria, sub-criteria and sub sub-criteria. Further more, the systematic effect of this process, can reduce the time taken to select a supplier